"… it is an absolute matter of impossibility that these townships will ever progress …" The growth (or not) of towns between 1900 and 1910 under the Native Townships Act 1895 - Schmidt, Tyson (Architectural History Aotearoa, 2025)
The majority of the 18 towns created under the Native Townships Act 1895 were formed in the first decade of the twentieth century. A continuation of the Crown’s support for settlers, the townships were also part of the modernisation push of the Liberal Government under Premier Richard Seddon. Neither city nor rural expanse, and certainly not the untamed bush, the townships were the servants of the farm and the stopovers for the tourist. The growth of the townships quickly slowed through a lack of access to financing and the taihoa policies of leading Māori MPs. The number of new townships being created reduced considerably by the end of the 1910s, and many that had been established struggled to reach their intended and expected potential. The story of native townships has only really been told through Waitangi Tribunal research, framed through a narrative of claim and a focus on two or three townships in a region at a time. This paper is an exploration of Native Townships and the stories they may hold from a landscape and architectural point of view.